Searching Malay text using stemming algorithm - Saian, Rizauddin; Ku-Mahamud, Ku Ruhana (Universiti Utara Malaysia Press, 2004)
Stemming is an important process to improve performance of a search engine by reducing the variant word forms to common forms. This paper evaluates the retrieval effectiveness of stemming algorithm in searching and retrieving relevant Malay web pages based on user natural query words. The retrieved web pages are weighted and ranked using inverse document frequency function. The retrieval effectiveness is measured using standard recall and precision. Experiments performed show that searching with stemming improves retrieval effectiveness when compared to searching without stemming algorithm.